Clinical Presentation of Painful Musculoskeletal Conditions at Community Level - Alam, Md Zahangir; Uddin, Mohammad Moin; Khan, Aminuddin A; Hossain, Shawkat; Jalil, Md Abdul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2017)
Background: This study was done in the community level to investigate the frequency of clinical manifestations of painful musculoskeletal conditions that present to the primary care physicians and to see the variations of musculoskeletal diseases in relations to age, gender and occupation. Methods: This was a crosssectional study. People with painful musculoskeletal conditions included and data were collected once. 107 patients with pain and musculoskeletal complaints were included in this study. Results: Majority (44.85%) presented with back pain. The commonest type of disease was degenerative (51.40%).15 cases (14.02%) of musculoskeletal pain were of inflammatory type. Peak age at presentation of musculoskeletal diseases was 40-49 years, which included 23.36% of total participants. 57.94% of the patients with musculoskeletal diseases were females. Among people of all occupations housewives constituted 52.33%. Conclusions: Low back pain is found as the commonest painful musculoskeletal problem encountered by the primary care physicians. Neck and shoulder pains are the next common problems. Housewives are the most vulnerable to musculoskeletal problems. A considerable number of inflammatory musculoskeletal diseases are also present at primary care level. Chatt Maa Shi Hosp Med Coll J; Vol.15 (2); Jul 2016; Page 49-51